2017
DOI: 10.1080/01480545.2017.1343342
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide genotoxicity in cotton picking women in Pakistan evaluated using comet assay

Abstract: To control agricultural pests and meet the increasing food demands, pesticides use has been increased substantially over time. Although pesticides are relatively specific to their targets, they can affect non-target organisms and are hazardous for the population around the application areas particularly to the individuals engaged in different types of agricultural activities. This situation is worse in developing and under-developed countries where personal protective equipment is merely used and regulatory gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 57 publications
3
14
1
4
Order By: Relevance
“…The non-usage of PPE during pesticide handling was also pointed out in other studies ( Pasiani et al, 2012 ; García-García et al, 2016 ; Ali et al, 2018 ; Godoy et al, 2019 ; Bernieri et al, 2019 ). Farmworkers reported that PPE is poorly tolerated because of high cost and discomfort when used in warm weather, similar to other studies conducted in tropical areas ( Recena et al, 2006 ; García-García et al, 2016 ; Caldas, 2016 ).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The non-usage of PPE during pesticide handling was also pointed out in other studies ( Pasiani et al, 2012 ; García-García et al, 2016 ; Ali et al, 2018 ; Godoy et al, 2019 ; Bernieri et al, 2019 ). Farmworkers reported that PPE is poorly tolerated because of high cost and discomfort when used in warm weather, similar to other studies conducted in tropical areas ( Recena et al, 2006 ; García-García et al, 2016 ; Caldas, 2016 ).…”
Section: Discussionsupporting
confidence: 71%
“…Such findings demonstrated an influence of PPE's effectiveness in preventing the genotoxic effects of pesticides on peripheral blood cells ( Simoniello et al, 2008 ). Previous studies have shown the same correlations between PPE use, intoxication, age and gender on level of DNA damage and suggested to be due to differences in exposure conditions, DNA repair capability and lifestyle factors ( Simoniello et al, 2008 ; How et al, 2015 ; Ali et al, 2018 ; Cayir et al, 2019 ). According to Ali et al (2018) , women from Bahawalpur District, of the Punjab province, in India, exposed to pesticides while picking cotton with bare hands, presented increased DNA damage when compared to controls.…”
Section: Discussionmentioning
confidence: 64%
“…In addition, we observed a significant increase in the score of 4 (greater damage) in the comet assay in all exposed groups, except in the group exposed to low oral concentration of 2,4-D, regardless of the route of exposure. Previous studies with long-term human exposure to pesticides have shown an increase in the tail length of comets in the exposed groups (Ali et al, 2018) and an increase in the number of micronuclei in exfoliated oral epithelial cells (Tomiazzi et al, 2018). Although it was not statistically significant, we observed a slight increase in micronucleus number in acute exposure of animals exposed to high concentration in the 72 hr interval but with damage recovery after 192 hr of exposure.…”
Section: Discussioncontrasting
confidence: 65%
“…These DNA loops are similar to chromatin loops as in the cell nuclei and represent the extent of DNA damage (Solmaz and Kovalak, 2018). Comet assay has been used widely for environmental monitoring, to test newly developed drugs, food additives and also used for the monitoring of DNA repair by living organisms (Ali et al, 2018, Bankoglu et al, 2018, Bastaki et al, 2017). The benefits of comet assay include its applicability to various tissues and/or special cell types, its sensitivity for detecting low levels of DNA damage, its requirement for small numbers of cells per sample, general ease of test performance, the short time needed to complete a study and its relatively low cost.…”
Section: Introductionmentioning
confidence: 99%